Trazabilidad microbiológica de enterobacterias presentes en sitios poco monitoreados y contaminados con arsénico provenientes de fuentes naturales a 3747 msnm en la parroquia de Toacaso. - Moposita Toapanta, Esthela Mireya (2022)
Toacaso is located in Cotopaxi province which has a high-water contamination with arsenic of natural origin from the Iliniza. The Development of this research Project is focused on establishing the microbiological traceability of enterobacteria in poorly monitored sites contaminated with arsenic at an altitude of 3700 to 3800 meters above sea level in Toacaso. During this research biophysical characterization of climate precipitation, temperature, slope, hydrogeology vegetation cover, agroecology, texture, taxonomy and soil erosion was carried out. Based on the physical, chemical and microbiological analyses of pH, dissolved oxygen, sulfates, manganese, arsenic and coliforms, a comparison was made with Ministerial Agreement 097 A and NTE INEN 1108. For the relationship of enterobacteria with arsenic, a sample was taken, culture media and Gram staining were used for their identification. The results showed that physical factors help arsenic to move in this area, due to its geological formation of volcanic and cangahua origin, with slopes of 15 – 25 moderately undulating and > 70 Mountainous. Laboratory analyses compared to Ministerial Agreement 095 A indicate that the parameters are within the maximum permissible limits for agricultural or irrigation use and for human consumption. However, the INEN Standard indicates that arsenic exceeds the limits established for water for human consumption. Finally, the relationship that exists between enterobacteriaceae and arsenic, gives as a possible result Escherichia, since the microbial culture and Gram staining shows Gram negative bacilli. The conclusion is that the arsenic contamination is of natural origin which exceeds the maximum permissible limits in the NTE INEN 1108 Standard, therefore the enterobacteria can support arsenic concentrations presented in the water of the Talahuachana stream.